Observational study of the differential impact of time-varying depressive symptoms on all-cause and cause-specific mortality by health status in community-dwelling adults: the REGARDS study. Issue 1 (5th January 2018) - Moise, Nathalie; Khodneva, Yulia; Jannat-Khah, Deanna Pereira; Richman, Joshua; Davidson, Karina W; Kronish, Ian M; Shaffer, Jonathan; Safford, Monika M
Abstract : Objective: To assess the association between time-varying depressive symptoms with all-cause and cause-specific mortality. Design: The REGARDS (Reasons for Geographic and Racial Differences in Stroke) is a national, population-based longitudinal study conducted from 2003 to 2007. Setting: General continental US communities. Participants: 29 491 black and white US adults ≥45 years randomly sampled within race–sex–geographical strata. Exposure: Elevated depressive symptoms (Centre for Epidemiologic Studies Depression (CES-D) 4≥4) measured at baseline and on average 5 and 7 years later. Main outcome measures: Cox proportional hazard regression models assessed cancer, non-cardiovascular (cardiovascular disease (CVD)), CVD and all-cause mortality. Results: The average age was 64.9 years; 55% were women; 41% black; 11.0% had elevated depressive symptoms; 54% had poor, fair or good health. Time-varying depressive symptoms were significantly associated with non-CVD (adjusted HR (aHR)=1.29, 95% CI 1.16 to 1.44) and all-cause (aHR=1.24, 95% CI 1.14 to 1.39), but not cancer (aHR=1.15, 95% CI 0.96 to 1.38) or CVD (aHR=1.13, 95% CI 0.98 to 1.32) death adjusting for demographics, chronic clinical diseases, behavioural risk factors and physiological factors. Depressive symptoms were related to all-cause (aHR=1.48, 95% CI 1.27 to 1.78), CVD (aHR=1.37, 95% CI 0.99 to 1.91), non-CVD (aHR=1.54, 95% CI 1.24 to 1.92) and cancer (aHR=1.36, 95% CI 0.97 to 1.91) death in those who reported excellent or very good health. The analyses of the association between one measure of baseline depressive symptoms and mortality analyses yielded similar results. Conclusions: Time-varying depressive symptoms confer an increased risk for all-cause mortality, CVD, non-CVD death and cancer death, particularly in those with excellent or very good health. These findings may have implications for timely treatment, regardless of health status.